1992
DOI: 10.1002/food.19920360405
|View full text |Cite
|
Sign up to set email alerts
|

Feeding differently processed soya bean Part 1. Effect on performance, protein utilization, relative organ weights, carcass traits and economics of producing broiler‐chickens

Abstract: The comparative utilization of differently processed (roasted, cooked and oil cake) soya bean base diets and groundnut cake diet were evaluated in a feeding trial using 100 day-old Anak broiler-chicks. The response criteria included performance, protein utilization, relative organ weights, carcass traits and economy of production. At the end of the feeding trial, the average weight gains of chicks fed processed soya bean diets were significantly (P less than 0.05) higher than those fed groundnut cake and raw s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…This observation is contrary to the protein content improvement observed with germination processing method of producing the blend (Table 1). Meanwhile, a previous study had reportedly linked the association of low PCV, RBC and serum protein with protein deficiency (Aletor and Egberongbe 1992). Thus, the high PCV and RBC but low WBC of the rats fed on the current blends relative to cerelac showed that the blends possessed the greater potentials of blood, antibody and cell-mediated immunity formation (Ijarotimi et al 2015).…”
Section: Hematological Characteristics Of Rats Fed With the Formulatementioning
confidence: 92%
“…This observation is contrary to the protein content improvement observed with germination processing method of producing the blend (Table 1). Meanwhile, a previous study had reportedly linked the association of low PCV, RBC and serum protein with protein deficiency (Aletor and Egberongbe 1992). Thus, the high PCV and RBC but low WBC of the rats fed on the current blends relative to cerelac showed that the blends possessed the greater potentials of blood, antibody and cell-mediated immunity formation (Ijarotimi et al 2015).…”
Section: Hematological Characteristics Of Rats Fed With the Formulatementioning
confidence: 92%
“…Details of the various processing techniques of the soya beans used, as well as the gross and proximate chemical composition of the experimental diets are presented in Part 1 of this study [4]. There were five diets comprising a conventional groundnut cake diet -D1, while diets 11-V comprised raw soya bean (RSB), roasted soya bean (RtSB), cooked soya bean (CSB) and soya bean oil cake (SBC), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…This is in consonance with earlier reports [9, 131 that total serum protein is positively correlated with dietary protein quality. This may explain, in part, the higher "operative" PER values obtained for chickens fed processed soya bean than for those fed the RSB in Part 1 of these studies [4]. The TSP values were highest in the chickens fed SBC diets and least in those fed RSB.…”
Section: Discussionmentioning
confidence: 75%
“…cooking, roasting and oil cake) are as described in Part 1 of this study [4]. The basal as well as the proximate chemical composition of the experimental diets are similarly presented [4].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation